The development of China's R&I system in the past 10 years - Rainer Frietsch (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
This discussion paper intends to describe the current status of the Chinese science and innovation system - mainly on the national level - as well as the developments of the past about 10 years that led to this current status.
urn:nbn:de:0011-n-5829788
Keywords: 330; Technologiepolitik; Innovationssystem; Forschungsfinanzierung; China (Grenzregion)